Training To Build Creativity And Entrepreneurial Innovation For Students Smk Swasta Buddhist Manjusri Pematangsiantar - Marto Silalahi; Julyantri Julyantri; Musa F Silaen; Novita Butarbutar; Elly Susanti (International Journal Of Community Service, 2022)
The purpose of this training activity is so that young people, especially students of SMK Swasta Buddhist Manjusri Pematangsiantar have the spirit and mental readiness in entrepreneurship, dare to think creatively and innovate and become job creators in the ministry. The method of activity carried out with a lecture model by providing an understanding of the understanding and principles of creativity, creative processes and techniques, basic concepts of innovation and innovative thinking, creativity and innovation in entrepreneurship, Head of The Secretary of SMK Swasta Buddhist Manjusri Pematangsiantar is very appreciative of the training, because with the presence of academics in providing training, the understanding of entrepreneurial concepts that will be a reference and foundation in the self-development and creativity of students.